A Possible Causative Mechanism of Raton Basin, New Mexico and Colorado Earthquakes Using Recent Seismicity Patterns and Pore Pressure Modeling. Issue 10 (21st October 2017) - Nakai, J. S.; Weingarten, M.; Sheehan, A. F.; Bilek, S. L.; Ge, S.
Abstract: The Raton Basin had the highest number of earthquakes in Colorado and New Mexico from 2008 to 2010. The rate of both wastewater injection and earthquakes in the basin increased dramatically starting in 1999 and 2001, respectively. We compare seismicity ( M L 0.0–4.3) in the Raton Basin from 2008 to 2010 with the location of modeled pore pressure increases, estimated from cumulative wastewater injection volume beginning at the onset of well injection to present for all 28 injection wells in the basin. We find that modeled pore pressures in the New Mexico portion of the basin (above 0.08 MPa) reached that necessary to induce seismicity (0.01–0.1 MPa). We simulate a fault plane, 20 km long, inferred from seismicity in Vermejo Park (1355 of 1881 total earthquakes), in our model. We find that the relatively permeable fault allows pressures to migrate deeper into the basin at the onset of our study in 2008, providing an explanation for the observed seismicity in the basement. The Tercio lineament of earthquakes is similar to Vermejo Park fault in strike, but has fewer earthquakes (129) and is shorter in length (9 km). Seismicity in Vermejo Park occurs continuously, but earthquakes occur episodically in the remainder of the basin. The number of earthquakes we observe in seven seismic clusters increases as the cumulative injected volume from wells within 5 km increases. The modeled pore pressures, earthquake locations, and relationship between cumulative volume and number of earthquakes indicate that seismicity in the Raton Basin is likely induced. Key Points: We infer a 20 km long Vermejo Park fault from seismicity that shows pore pressure changes of 0.08 MPa by 2008 Pore pressure modeling shows changes up to 0.50 MPa, despite an underpressured disposal interval not in direct contact with the basement The number of earthquakes and cumulative volume of wastewater injected are correlated for wells within 5, 10, and 15 km of seismicity